2019
DOI: 10.1080/1828051x.2019.1593057
|View full text |Cite
|
Sign up to set email alerts
|

Use of Spline function for the characterisation on peak yield, peak day and persistency in lactation curves in Murciano-Granadina goats

Abstract: The objective of this study was to characterise the peak yield (PY), peak day (PD) and the persistency (P) of the lactation curve of Murciano-Granadina goats by Spline considering the variation factors (region, type of kidding, lactation number and season) and their levels. A total of 1,349,347 test-day records from 180,872 lactations, of 85,404 goats were used. The analysed data with Spline model was considered for adequate fit in lactation curves for others traits in these goats. All factors affected the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This estimate is greater than those of 1.29 kg, 2.4 kg, and 1.1 kg that reported by Ayasrah et al (2013) The PW was attained at the fifth week (5.09±0.08 weeks, Table 1), which is higher than 3.9 weeks and 3.1 weeks reported by Ayasrah et al (2013) and Mousa et al (2016) in Damascus goats in Jordan and Aradi goats in Saudi Arabia, respectively. On the other hand, higher estimate of 7.14 weeks was observed by Miranda-Alejo et al (2019) in Murciano-Granadina goats in Spain.…”
Section: Lactation Curve Traitsmentioning
confidence: 77%
See 1 more Smart Citation
“…This estimate is greater than those of 1.29 kg, 2.4 kg, and 1.1 kg that reported by Ayasrah et al (2013) The PW was attained at the fifth week (5.09±0.08 weeks, Table 1), which is higher than 3.9 weeks and 3.1 weeks reported by Ayasrah et al (2013) and Mousa et al (2016) in Damascus goats in Jordan and Aradi goats in Saudi Arabia, respectively. On the other hand, higher estimate of 7.14 weeks was observed by Miranda-Alejo et al (2019) in Murciano-Granadina goats in Spain.…”
Section: Lactation Curve Traitsmentioning
confidence: 77%
“…They attributed that, does kidded in winter had a lower milk production at starting lactation, therefore, they could maintain milk yield for a longer time compared to those kidded in spring. Miranda-Alejo et al (2019) mentioned that the P % was the lowest in spring and the highest in fall in Murciano-Granadina goats in Spain. While Bermejo et al (2020) found that the P % was highest in autumn kidding in Murciano-Granadina goats in Spain.…”
Section: Month Of Kiddingmentioning
confidence: 99%